IMPROVEMENT THE XGBOOST MODEL IN DETERMINING NBA GAME WIN DETERMINANTS: A BAYESIAN HYPERPARAMETER OPTIMIZATION AND SHAP APPROACH - Fija Ramadhan; Ahmad Zainul Fanani (RADJA PUBLIKA, 2026)
In the era of modern sports analytics, post-game team performance evaluation is often conducted subjectively. This study aims to develop an objective diagnostic model to identify the key technical–statistical factors that determine victories in the NBA, grounded in the principle of game efficiency. Using box-score statistical data from the 2004–2024 seasons, this research employs the Extreme Gradient Boosting (XGBoost) algorithm [2], optimized through the Tree-structured Parzen Estimator (TPE) method within the Optuna framework [3], to classify game outcomes. The experimental results demonstrate highly precise model performance, achieving an accuracy of 95.2% and an F1-score of 0.96. Interpretability analysis using the SHAP (Shapley Additive exPlanations) method [4] reveals that dominance in Shooting Efficiency (EFG%) and Player Impact Estimate (PIE) constitutes the absolute determinants of victory, followed by the minimization of turnovers. Furthermore, counterfactual simulations provide diagnostic insights indicating that an increase in a single statistic (e.g., +5 assists) without a corresponding improvement in shooting efficiency actually reduces the probability of winning (from 0.61 to 0.26). This finding suggests the phenomenon of “empty assists,” where ball movement does not translate into effective scoring opportunities. This study contributes a performance-auditing framework that enables coaches and analysts to retrospectively evaluate the effectiveness of game strategies in an objective and data-driven manner